Is your purchase intention influenced by irrational factors? An investigation of fashion industry - Muhammad Tahir Jan; Ahmed Mohamed Hamed Aly Abouzaid; Nadeem; Tashpia Hossain (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2020)
This research paper mainly aims to identify and analyse irrational factors that impact consumers' purchase intention, especially in the fashion industry. The data for this study were collected from 205 consumers of various nationalities via an online self-administered questionnaire. The acquired data were put through a thorough process to establish their relevance and to ensure that the data were ready for further analysis by applying the SPSS & AMOS software. Three irrational factors were extracted from the extant literature, namely, media, social impact, and emotions. These factors are reported to have a positive influence on the consumer's purchase intention. First, a descriptive analysis was undertaken followed by an inferential analysis. Structural equation modelling (SEM) was used to test the fitness of the proposed model and also to test the hypotheses. Two out of the total three hypotheses are supported. In this case, media influence and social influence emerged with a significant positive impact on the consumer's purchase intention. Even though emotions influence resulted in a positive impact, it was not statistically significant and does not relate to the consumer's purchase intention in the fashion industry. The findings of this study have significant contribution to the body of knowledge and practice. Marketing research, in general, and consumer research, in particular, will benefit from the contribution of this research. Similarly, policy makers in the fashion industry may adopt the findings of the present study to devise more effective marketing strategies. Indeed, this research highlights that the consumer's purchase intention is not entirely in response to a particular phenomenon but a multitude of so-called "irrational" factors like media, society, and emotions.
Keywords: D1; M1; M3; 650; Irrational factors; purchase intention; fashion industry; SEM